Nanotechnologies and Nanomaterials in 3D (Bio)printing toward Bone Regeneration. Issue 11 (11th August 2021) - Wang, Zongliang; Agrawal, Prajwal; Zhang, Yu Shrike
Abstract : The utilization of biomedical nanotechnologies and nanomaterials has surged in the field of 3D bone printing and bioprinting. As such, it is possible to reproduce the hierarchical structures and compositions of the native bone‐related tissues, allowing for regulating cell behaviors and tissue formation toward bone tissue engineering. The use of nanobiomedical systems may also enhance the shape fidelity and printability apart from endowing plentiful biological functions to the (bio)inks. Herein, first, the recently published literature on nanotechnologies and nanomaterials utilized for 3D bone (bio)printing is overviewed. Later, recent progress and challenges for osseous interface and vascularized bone reconstructions are discussed. Finally, the future prospectives and potential commercialization for 3D‐(bio)printed personalized bone implants are proposed. Abstract : Herein, the biomedical nanotechnologies and nanomaterials utilized in 3D printing and bioprinting for bone regeneration are discussed. An elaboration on the advances and challenges in the recapitulation of musculoskeletal interfaces, reinforcements of 3D‐printed/bioprinted bone constructs, reconstruction of microvascular networks, and osteogenic differentiation is given. Perspectives on the applications of 3D printing/bioprinting applications in bone tissue engineering and personalized medicine are summarized.